Published versus Unpublished Dissertations in Psycho-Oncology Intervention Research - Moyer, Anne (2010)
OBJECTIVE: There are conflicting views regarding whether gray literature, including unpublished doctoral dissertations, should be included in systematic reviews and meta-analyses. Although publication status frequently is used as a proxy for study quality, some research suggests that dissertations are often of superior quality to published studies. METHODS: We examined 107 projects involving doctoral dissertations (42 published, 65 unpublished) that studied psychosocial interventions for cancer patients. RESULTS: Published dissertations were more likely to be supported by research funding but were not more likely than unpublished dissertations to examine specific types of interventions. Across several indices of methodological quality there were minimal differences. Dissertations with significant findings tended to be more likely to be published than those without significant findings. CONCLUSIONS: Unpublished dissertations focusing on psychosocial interventions for cancer patients are not necessarily of vastly inferior quality to those that eventually are published. Because doctoral dissertations are easy to access relative to other forms of gray literature, are free from some types of bias, and are reported thoroughly, they merit inclusion in comprehensive literature reviews.